Effects of reduction process on the electrochemical and microstructural properties for electrolyte-supported SOFC. (21st January 2015) - Cheng, Shih-Wei; Tsai, Chun-Huang; Wu, Szu-Han; Liu, Chien-Kuo; Cheng, Yung-Neng; Lee, Ruey-Yi
Abstract Reduction process plays an important role before solid oxide fuel cells (SOFCs) start to work. The reduced anode must have enough porosity for transferring the fuel gases and good conductivity for decreasing the area specific resistance. To investigate how the reduction process affects the electrochemical and microstructural properties for electrolyte-supported SOFC with a nickel oxide/yttria-stabilized zirconia (NiO/YSZ) anode, three different reduction processes are applied to the same batch of cells in this paper. Process I for one of tested cells is to introduce a dilute gas of 20% hydrogen and 80% nitrogen to the anode side at room temperature. Process II and III for the others are to introduce the same dilute gas while the cells are heated up to 800 and 700 °C respectively. Although the Process I provides much time to reduce the anode of the cell, the resulting performance is lower than the others. AC impedance analyses show that the cell reduced at higher temperature has lower ohmic and polarization resistance. Moreover, the differences of nickel connection and particle size on the anode are observed in microstructure of the cells, which proves that reduction process has a vital effect for solid oxide fuel cells.